Dilema da formação matemática em Angola: falta de iniciativas próprias ou de compromisso com a qualidade de ensino? - Wongo Gungula, Eurico; Faustino, Arnaldo (Universidad de Costa Rica, 2018)
This article aims to address the dilemma of mathematical training in Angola through criteria’s issued by university students and teachers, due to insufficient social awareness of the need to improve the quality of mathematics teaching at all educational levels and subsystems. This approach allowed us to identify aspects which made it possible to understand and explain the trajectory in this field, not only to restructure the way it interrelates the academic, technical and investigative components but also to better understand the Angolan mathematical reality, placing it between epistemological, methodological and technological approaches that allows to trigger and control the elements, factors, characteristics, contradictions and strategies that contribute to the qualitative transformation of this process. The methodological procedure followed in the development of this article was mixed and essentially grounded on research action as a type of qualitative research based on the observation of the phenomena associated with action and problem solving, where the active and committed participation of the researcher and others involved in the process plays a key role in transforming this dynamic. The results indicates that although teachers currently attribute greater relevance to contextual factors that stimulate the construction of significant mathematical knowledge for students, they coincide in the need to continually increase the levels of contextualization of contents at all educational levels and subsystems of teaching, an aspect that contributes to the development of a social and institutional awareness about the appropriateness of the improvement of the Mathematics teaching quality in Angola.